2015
DOI: 10.1111/eth.12376
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Inclusive Sexual Selection in the Ant Cataglyphis cursor: Worker Aggressions Differentially Affect Male Access to Virgin Queens

Abstract: Sexual selection typically shapes the traits of individuals capable of reproduction. However, in social species, it may also affect the behaviour of non‐reproductive individuals if this increases their inclusive fitness. We examined the potential role of workers during mating in the polyandrous ant Cataglyphis cursor. In this species, mating takes place on the ground near the nest entrance, and workers chase away foreign males trying to mate with young queens (gynes). We investigated the effects of worker aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Multiple mating by queens and males sets the stage for sexual selection. In species producing new colonies by colony fission (see Section 3.2), mating occurs near the nest entrance where workers may affect precopulatory mate choice (73,74). Moreover, sperm competition may generate intense directional selection on sperm traits that enhance fertilization success, such as sperm production and size (16).…”
Section: Sociogenetics and Unusual Reproductive Systemsmentioning
confidence: 99%
“…Multiple mating by queens and males sets the stage for sexual selection. In species producing new colonies by colony fission (see Section 3.2), mating occurs near the nest entrance where workers may affect precopulatory mate choice (73,74). Moreover, sperm competition may generate intense directional selection on sperm traits that enhance fertilization success, such as sperm production and size (16).…”
Section: Sociogenetics and Unusual Reproductive Systemsmentioning
confidence: 99%
“…Another possible mechanism related to precopulatory sexual selection may involve altering acceptance threshold making males able to get closer to gynes without being harassed by workers (Helft et al 2016; Helft et al 2015). There is, indeed, evidence of males mimicking the queen’s chemical bouquet in ants, thus allowing them to escape aggression from other males (Cremer et al 2002) or from workers (Franks and Hölldobler 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of workers in mate choice has been suggested in army ants (Franks & Hölldobler 1987), Argentine ants (in the invasive range, Sunamura et al 2011) and the facultatively parthenogenetic ant Cataglyphis cursor (Cronin et al 2011;Helft et al 2015). In the latter two species, workers are aggressive towards all foreign males who enter or come near the nest searching for a receptive gyne.…”
Section: Introductionmentioning
confidence: 99%
“…This is indeed what occurs in C. cursor. Gynes are produced by the multiply mated queen (Lenoir et al 1988;Pearcy et al 2004) and workers are highly related to both parthenogenetically produced gynes (clones of their mother, r ~ 0.5) and sexually produced gynes (r = 0.44 on average) (Doums et al 2013), and a recent study showed that worker aggression toward males affected male relative mating potential, increasing it for lighter males and decreasing it for heavier males (Helft et al 2015). The present study therefore aims at determining whether C. cursor gynes exercise pre-copulatory mate choice or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation